The state of impact investment in Latin America: an exploratory study based on the country analysis of Brazil and Mexico - Berkenheide, Peter (2019)
The increasing awareness of sustainability has also taken hold into the financial sector. New investment strategies that aim to integrate economic value creation with investors´ moral believes are on the rise. Impact investing is one type of investing that seeks to support social entrepreneurs to scale their operations. Few big international investors dominate the impact investing, which is still a niche market. This study compares the industry´s developments and challenge on a global scale with those on a local scale in Latin America, especially in Brazil and Mexico. Therefore, this study combines and compares different datasets provided by the Global Impact Investing Network (GIIN) and the Association for Private Capital Investments in Latin America (LAVCA). Moreover, qualitative interviews with industry experts, such as social entrepreneurs and impact investors, help to generate a deeper understanding of the status quo, the challenges, and opportunities of impact investing in Latin America. This study finds that impact investing in Latin America, so far, works as a subcategory of specialized venture capital and private equity. Impact investing funds have identified a niche market that allows them to invest in companies that they expect to generate both financial returns and social impact. Success stories of current investments will be crucial to develop the local industry further and to reduce the dominance of foreign investors in Latin America. With increasing maturity, industry experts expect impact investing to differentiate itself from traditional venture capital and private equity through more exotic financial options, such as revenue-based lending and loan guarantees.